Penyuluhan kesehatan tentang penyakit reumatik pada lansia - Riona Sanjaya; Hamid Mukhlis; Hellen Febriyanti (JOURNAL OF Public Health Concerns, 2021)
According to the World Health Organization (WHO), rheumatoid arthritis sufferers worldwide reached 355 million in 2009, meaning that 1 in 6 people in the world suffer from Rheumatoid Arthritis. Rheumatism is a disease that attacks the moving limbs, namely the parts of the body that are connected to each other by joints causing pain. Various factors can cause a high incidence of rheumatism, one of which is a behavioral factor that is not in accordance with health principles. Behavioral factors are very important to pay attention to so that they can reduce the incidence of disease. The purpose of counseling is to understand rheumatism as a factor, signs and symptoms, and the importance of rheumatism treatment. Participants who attended were 5 people consisting of 2 men and 3 women. The place is used according to the plan made using the tools during the socialization, such as flipcharts and leaflets. The results of this activity can increase public knowledge about rheumatic diseases. Keywords: Rheumatism; Society; Health counseling; Health promotion. Menurut World Health Organization (WHO) Penderita Reumatoid Arthritis diseluruh dunia mencapai angka 355 juta jiwa di tahun 2009, artinya 1 dari 6 orang didunia ini menderita Reumatoid Arthritis. Rematik adalah penyakit yang menyerang anggota tubuh yang bergerak, yaitu bagian tubuh yang berhubungan antara yang satu dengan yang lain dengan perantaraan persendian, sehingga menimbulkan rasa nyeri. Penyebab tingginya angka kejadian reumatik dapat diakibatkan oleh berbagai faktor baik faktor yang tidak dapat dimodifikasi ataupun faktor yang dapat dimodifikasi. Tujuan dari penyuluhan memahami tentang penmyakit reumatik berupa faktor, tanda dan gejala, dan pentingnya pengobatan reumatik. Peserta yang hadir sebanyak 5 orang yang terdiri dari 2 laki-laki dan 3 perempuan. Tempat yang digunakan sudah sesuai dengan rencana yang telah dibuat dengan menggunakan perlengkapan selama penyuluhan seperti lembar balik dan leaflet. Hasil dari kegiatan ini dapat meningkatkan pengetahuan masyarakat tentang penyakit reumatik.